CLOZE PASSAGE IN IMPROVING STUDENTS’ READING COMPREHENSION - Yanuarti Apsari (Eltin Journal : Journal of English Language Teaching in Indonesia, 2016)
Using an effective practice of comprehending English text is another effort to improvereading comprehension of EFL students, especially the Indonesian students. Thus, thisstudy aims to see whether there is a difference in performance when students practiceregularly with cloze passages and practice with passage in full but followed by carefully written comprehension questions. Regarding the purpose of the research, anexperimental research is used where thirteen pairs of students from two groups areobserved. The data are collected from pre-test and post-test. Quantitative dataobtained is statistically analyzed and then compares by using t-test with paired samplestatistics. The result of the study reveals that Students treated by cloze passagessignificantly better than students treated by full passages in terms of readingcomprehension ability. It is evidently clear that cloze is an essential teachingtechnique that fosters reading comprehension. Therefore, it is recommended thatKeywords: Cloze Passage and Reading Comprehension